استـــــــــــــخدام عمليـــــــــــة التحليــــــــــــل الهرمي فـــــــــــي اختيــــــــــار موقـــــــــــع الشركــــــــــــــــــــة (Journal of Accounting and Financial Studies ( JAFS ), 2012)
The location s of a company has been attracting the attention of many researchers in various industrial, services, economic and social field, which consequently inspired the scientists to published number of articles and studies concerning the criteria, influencing factors and quantitative methodologies for the location. For example goal programming, fuzzy logic and genetic algorithm method logic. However, the failure of these methodologies to integrate the qualitative and quantitative factors for the location decisions, justified the use of AHP, which developed by saaty in 1970, to overcome the complicated issues 0f several measures, saaty has shown explicitly the significance of this technique in resolving the problems of application. The fundamental of the technique is based on the relative importance of each factor according to decision maker’s estimation and the translation of these estimated elements into digital value, which assign the priorities of the decision maker. This research aims to work out a theoretical frame about location decision and the role of AHP as a multi- criteria tool in choosing suitable locations.